2016
DOI: 10.1038/srep19147
|View full text |Cite
|
Sign up to set email alerts
|

Ncl Synchronously Regulates Na+, K+ and Cl− in Soybean and Greatly Increases the Grain Yield in Saline Field Conditions

Abstract: Salt stress inhibits soybean growth and reduces gain yield. Genetic improvement of salt tolerance is essential for sustainable soybean production in saline areas. In this study, we isolated a gene (Ncl) that could synchronously regulate the transport and accumulation of Na+, K+, and Cl− from a Brazilian soybean cultivar FT-Abyara using map-based cloning strategy. Higher expression of the salt tolerance gene Ncl in the root resulted in lower accumulations of Na+, K+, and Cl− in the shoot under salt stress. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 43 publications
3
136
0
Order By: Relevance
“…This was similar to the previously reported salt tolerance phenotype of G. max (Tuyen et al, 2016), Brassica napus line N119 (Yong et al, 2014), Oryza sativa line FL478 (Walia et al, 2005), and Foxtail millet cv. Prasad (Puranik et al, 2011), all of which maintained lower Na + concentrations, and ratios of Na + /K + and Na + /Ca 2+ compared with sensitive lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was similar to the previously reported salt tolerance phenotype of G. max (Tuyen et al, 2016), Brassica napus line N119 (Yong et al, 2014), Oryza sativa line FL478 (Walia et al, 2005), and Foxtail millet cv. Prasad (Puranik et al, 2011), all of which maintained lower Na + concentrations, and ratios of Na + /K + and Na + /Ca 2+ compared with sensitive lines.…”
Section: Discussionsupporting
confidence: 91%
“…Maintenance of a low Na + concentration, and low ratios of Na + /K + and Na + /Ca 2+ are widely used as indices of plant salinity tolerance (Puranik et al, 2011; Yong et al, 2014; Tuyen et al, 2016). To evaluate the alkalinity tolerance of wild soybean N24852, the salt tolerant soybean variety Lee 68 was used for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the overexpression of Ncl gene (homologous to the Na + /H + antiporter gene family) into a Japanese soybean salt-sensitive cultivar Kariyutaka, resulted in improved salt tolerance in transgenic soybean. A close association was observed between the high expression of the salt tolerance gene Ncl in the root, the lower accumulation of Na + , K + , and Cl - in the shoot under salt stress and salt tolerance in the transgenic lines (Do et al, 2016). …”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 76%
“…This QTL is likely to be the Ncl locus based on pedigree tracing (Lee et al, 2004). Recently, the introgression of the tolerance allele Ncl into soybean cultivar Jackson, using DNA MAS, produced an improved salt-tolerant line (Do et al, 2016). …”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 99%
“…Haplotype screening of GmSALT3 identified a total of nine haplotypes including two salt-tolerant haplotypes and seven salt-sensitive haplotypes (Guan et al, 2014b). Recently, Do et al (2016) identified the same gene in salt tolerant cultivar FT-Abhayra using map-based cloning and identified same insertion of a ~3.8-kb Ty1/copia type retrotransposon fragment responsible for loss of function of the salt tolerant gene named as Ncl . All of the characterized genes underlying salt tolerant QTLs were pinpointed at single gene Glyma03g32900 , and the presence of Ty1/copia type retrotransposon in all salt tolerant genotypes indicate the single point of origin for salt sensitivity in soybean.…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 99%